2015
DOI: 10.1111/bjhp.12149
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in using cardiometabolic risk information among consumers with low health literacy

Abstract: What is already known on this subject? Online disease risk assessments have become widely available internationally. People with low SES and health literacy tend to participate less in health screening. Risk information is difficult to understand, yet little research has been carried out among people with low health literacy. What does this study add? People with low health literacy do not optimally use risk information in an online cardiometabolic risk assessment. The texts provided in the cardiometabolic ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 72 publications
0
26
0
2
Order By: Relevance
“…These scales were based on previous research, where factors related to intended participation in PCS for cystic fibrosis were studied. 24 Perceived severity was measured with four items on a 5-point scale (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Respondents were asked how disturbing it would be to have a child with either severe pain, severe physical disability or severe intellectual disability, or who would die at a young age.…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…These scales were based on previous research, where factors related to intended participation in PCS for cystic fibrosis were studied. 24 Perceived severity was measured with four items on a 5-point scale (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Respondents were asked how disturbing it would be to have a child with either severe pain, severe physical disability or severe intellectual disability, or who would die at a young age.…”
Section: Groupmentioning
confidence: 99%
“…This information is important because it is clear from previous research and clinical practice that risk information is difficult to understand and people may interpret it differently. [4][5][6][7] The factors that we examine are based on the Theory of Planned Behaviour (TPB), on previous research on intended participation in …”
mentioning
confidence: 99%
“…Although some risk formats (eg natural frequencies and some graphical formats in addition to numerical information) in general seem to evoke better risk understanding than other formats (eg percentages only), it remains unclear how the provided risk information supports an individual's understanding of their risk. Previous user tests have shown that risks presented as percentages in risk calculators often have unclear or ambiguous meaning for end‐users, even when accompanied by graphical information . Other more general problems revealed by such user tests are that the risk message does not necessarily match the individual's existing beliefs and expectations about risk factors, and that, perhaps partly as a result of this, many end‐users with relatively high risks tend to undervalue or normalize their risk .…”
Section: Introductionmentioning
confidence: 99%
“…Previous user tests have shown that risks presented as percentages in risk calculators often have unclear or ambiguous meaning for end‐users, even when accompanied by graphical information . Other more general problems revealed by such user tests are that the risk message does not necessarily match the individual's existing beliefs and expectations about risk factors, and that, perhaps partly as a result of this, many end‐users with relatively high risks tend to undervalue or normalize their risk . Such problems are particularly urgent as many people, not only those with lower educational levels, have poor health literacy and numeracy skills, thereby placing them at a higher risk of misinterpreting information and making non‐informed decisions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation